An Integrated distribution system for Deteriorating Items via an Artificial Intelligence Method - Jonas C.P. Yu (International Journal of Supply Chain Management, 2016)
This paper proposes a n-manufacturer-one- distributor-n-retailer single-period inventory model for deteriorating items that integrates three levels of distribution system. In order to achieve long-term benefits and global optimum of the system, the different facilities develop their partnership through information sharing and strategic alliances. The mathematical model describes how the integrated approach to decision making can achieve global optimum. Due to the complexity of the non-linear problems, it is not possible to find the global optimum analytically. Annealing is the physical process of heating up a solid until it melts followed by cooling it down until it crystallizes into a state with perfect lattice. Following this physical phenomenon, a Artificial Intelligence methodSimulated Annealing (SA), has been developed to find the global optimum for a complex cost surface through stochastic search process. A computer program in C-language has been developed for this purpose and is implemented to derive the optimum decision for the decision maker. Numerical examples and a sensitivity analysis are given to validate the results of the system. The proposed model has potential application in product distribution inventory systems.